Size ranges of magnetic domain states in tetrataenite - Mansbach, E; Shah, J; Williams, W; Maurel, C; Bryson, J; Weiss, B (American Geophysical Union, 2022)
Paleomagnetic studies of meteorites provide unique constraints on the evolution of magnetic fields in the early solar system. These studies rely on the identification of magnetic minerals that can retain stable magnetizations over ≳4.5 billion years (Ga). The ferromagnetic mineral tetrataenite (γ''-Fe0.5Ni0.5) is found in iron, stony-iron and chondrite meteorite groups. Nanoscale intergrowths of tetrataenite have been shown to carry records of paleomagnetic fields, although the effect of magnetostatic interactions on their magnetic remanence acquisition remains to be fully understood. Tetrataenite can also occur as isolated, non-interacting, nanoscale grains in many meteorite groups, although the paleomagnetic potential of these grains is particularly poorly understood. Here, we aim to improve our understanding of tetrataenite magnetization to refine our knowledge of existing paleomagnetic analyses and broaden the spectrum of meteorite groups that can be used for future paleomagnetic studies. We present the results of analytical calculations and micromagnetic modeling of isolated tetrataenite grains with various geometries. We find that tetrataenite forms a stable single domain state at grain lengths between 6 and ∼160 nm dependent on its elongation. It also possesses a magnetization resistant to viscous remagnetization over the lifetime of the solar system at 293 K. At larger grain sizes, tetrataenite's lowest energy state is a lamellar two-domain state, stable at Ga-scale timescales. Unlike many other magnetic minerals, tetrataenite does not form a single-vortex domain state due to its large uniaxial anisotropy. Our results show that single domain and two-domain tetrataenite grains carry an extremely stable magnetization and therefore are promising for paleomagnetic studies.